Influence of coil contact on static behavior of helical compression springs. Issue 1 (February 2021) - De Crescenzo, F; Salvini, P
Abstract: Large deformations of helical springs are affected by coil contact, but most available spring modelling techniques only account for nonlinear vertical motion, and Finite Elements (FE) nonlinear analysis that considers contact between coils can be very expensive. A 2D model based on equivalent beam and penalty-based contact algorithm is developed for efficient yet realistic prediction of non-uniform spring deflection. The proposed model is tested versus FE, where the helical wire is modelled using beam elements. Two scenarios are taken into account: a cylindrical spring in compression/bending and a progressive conical spring under simple compression. It is shown that the proposed model matches FE at a very low computational cost.